Analisis Yuridis Penanganan Kasus Narkoba Menurut Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika (Study Kasus Direktorat Reserse Narkoba Polda Sumatera Selatan) - Reza Pahlevy; M. Azza Nuhanda; Ade Rizky Amanda; M.Edho Reza Utama (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The impact of globalization in this modern era in addition to the economy also has an impact on crime, one of which is Drugs (Narcotics, Psychotropic, and other Addictive substances). The concern is not without reason, because from various mass media we can know together that the users of illegal drugs or drug users have increased to various levels of society. The methodology in writing this thesis is empirical juridical research where this research deals directly and is synchronized with legal principles and existing regulations. The investigation process of Ditres Narkoba is carried out in several stages, in accordance with the Standard Operating Procedure for handling drug crimes. First, reports or information are collected from the public. After that, an investigation task and warrant are made. Next, the information report is enhanced by using investigation methods such as inspection, surveillance, purchase under cover, and delivery control.